2018
DOI: 10.1186/s12917-018-1600-3
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of Muscovy duck parvovirus infection by TaqMan-based real-time PCR assay

Abstract: BackgroundMuscovy duck parvovirus (MDPV) causes high mortality and morbidity in Muscovy ducks, with the pathogenesis of the virus still unknown in many respects. Specific MDPV detection is often rife with false positive results because of high identity at the genomic nucleotide level and antigenic similarity with goose parvovirus (GPV). The objective of this study was to develop a sensitive, highly specific, and repeatable TaqMan-based real-time PCR (qPCR) assay for facilitating the molecular detection of MDPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Similarly, there was possible vertical transmission of N-GPV between breeder Cherry Valley and Pekin ducks to their ducklings [22, 23]. Classic MDPV shared the same phenomenon of possible vertical transmission, similar to our recent work [18]. In this study, we demonstrated that N-GPV appeared to possible vertically transfer from breeder Mule ducks to ducklings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, there was possible vertical transmission of N-GPV between breeder Cherry Valley and Pekin ducks to their ducklings [22, 23]. Classic MDPV shared the same phenomenon of possible vertical transmission, similar to our recent work [18]. In this study, we demonstrated that N-GPV appeared to possible vertically transfer from breeder Mule ducks to ducklings.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, a total of 52 NS gene sequences (37 GPVs and 15 MDPVs) were compared for primer and probe design. Previous studies showed that NS genes shared characteristic variations between GPVs and MDPVs that could be used to design more precise primers and probes [18, 19]. Using a similar strategy, a TaqMan real-time PCR for the detection and quantification of GPV was developed and evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time PCR is now widely used in clinical settings. Compared with loop-mediated isothermal amplification, enzyme-linked immunosorbent assay, and indirect immunofluorescence assay, quantitative real-time PCR has advantages with respect to time and sensitivity [ [27] , [28] , [29] , [30] ]. Quantitative real-time PCR also has higher sensitivity, specificity, and positive detection rates than traditional PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In checking to see the intra-batch repeatability, triplicates of each dilution were detected, and according to the formula of the geometric mean Cq values / standard deviation calculated the coefficients of variation (CV). The coefficient of variation for inter-assay repeatability shows the differences among the measures at different times [33]. Three repeats were performed for each of the inter and intra assay analysis.…”
Section: Repeatability Analysis Of the Rt-qpcr Assaymentioning
confidence: 99%